Review of crustal architecture and evolution in the Ungava Peninsula — Baffin Island area: connection to the Lithoprobe ECSOOT transect - St-Onge, M R; Scott, D J; Wodicka, N (Canadian Journal of Earth Sciences, 2002)
Within the Trans-Hudson Orogen in northern Quebec and southern Baffin Island, parautochthonous Archean basement and Paleoproterozoic cover, as well as allochthonous (accreted) Paleoproterozoic units, are exposed in a series of antiformal culminations and complementary synclinoria. The parautochthonous rocks of the Superior Province margin and two assemblages of accreted Paleoproterozoic units (Ungava and Meta Incognita crustal terranes) define a basic tripartite crustal architecture which is characterized by polyphase deformation and metamorphic histories. Early structures and mineral assemblages are recognized in all three crustal components and shown to be temporally distinct. The earlier structures and assemblages are overprinted by younger elements and mineral assemblages that are related to at least three regional contraction episodes and one thermal event that are common to all crustal components of the orogen. Close correlation of regional aeromagnetic data in northern Quebec and southern Baffin Island with the three crustal components offers a first-order approximation of the distribution of basement lithological units across Hudson Strait. Continuation of the aeromagnetic domains beneath Ungava Bay to northeastern Quebec and northern Labrador allows for the southward extrapolation of the tripartite Trans-Hudson Orogen crustal architecture into the Lithoprobe Eastern Canadian Shield OnshoreOffshore Transect area.